Pengaruh Media Sosial dan Video Konferensi terhadap Hasil Belajar Mahasiswa - Muhammad Khoirul Anam; Desty Endrawati Subroto; Nazswa Prenita Anggraini; Rifdah Rofiqoh (PT. Penerbit Tiga Mutiara, 2025)
This study aims to examine the influence of social media and video conferencing applications on the learning outcomes of students at Bina Bangsa University. In line with the rapid adoption of digital technology in the education sector, this research focuses on evaluating the effectiveness of social media and video conferencing apps in supporting flexible, interactive, and collaborative learning. Using a quantitative approach with descriptive and explanatory methods, data was collected from 50 respondents selected through stratified random sampling. The results indicate that WhatsApp is the most widely used social media platform by students (46.15%), while the most dominant video conferencing application is Zoom (61.54%). Students recognize the important role of social media in facilitating efficient communication, while video conferencing apps provide significant benefits in real-time interactivity. The combination of these two platforms has proven to significantly enhance students' learning motivation, with 84.62% of respondents acknowledging a positive impact on their learning process. This study emphasizes that the utilization of digital technology, such as social media and video conferencing apps, plays a crucial role in supporting more flexible and adaptive education. Therefore, the findings of this study recommend that educational institutions optimize the use of digital technology in learning to meet the demands of an evolving education system in this digital era.